Oil Prices Sensitivity to The Power Supply Procurement Project at PT PEP Sukowati - Pangestu, M. Agus; Utomo, Christiono; Ahyudanari, Ervina (IPTEK Journal of Proceedings Series, 2020)
This study intends to determine the sensitivity of changes in oil prices to investment in power supply projects from the financial aspect. The investment analysis conducted is an evaluation of Net Present Value (NPV) using the production sharing contract (PSC) model with a profit sharing system. Based on the analysis conducted, the sensitivity of changes in oil prices has a very significant effect on the project NPV. Changes in oil prices by 60% from the base case to US $ 80 caused NPV to rise by 183%. But on the contrary if the price of oil touches the figure of US $ 20 or -60% from the base case, it will make the NPV negative, so the project is not economical to proceed. In addition, it know that the acceptance limit of investment in power supply projects is at oil prices greater than US $ 34 per barrel. This significant change in both the decline and increase in oil prices to the NPV is very logical because oil prices determine the amount of revenue earned from this project.